Efektivitas Simulasi Bencana terhadap Kesiapsiagaan Bencana Gempa Bumi dan Tsunami pada Siswa SMPN 1 Soropia di Wilayah Pesisir Kecamatan Soropia Kabupaten Konawe: The Effectiveness of Disaster Simulation on Disaster Preparadness for Students of SMPN 1 Soropia about Eartquake and Tsunami in the Coastal Area, Soropia District, Konawe Regency - Sari Arie Lestari; Islaeli Islaeli; Islamiah Islamiah; Anisa Purnamasari; Wa Ode Aisa Zoahira (Jurnal Surya Medika (JSM), 2022)
Southeast Sulawesi Province is often haunted by various kinds of disasters. In the last 3 years, the city of Kendari and its surroundings has experienced earthquake activity ranging from large to low scale, causing unrest for the community. Soropia sub-district is located in the coastal area, whose activities, the people are in the coastal area. Making this area very vulnerable to earthquakes and tsunamis. The purpose of this study was to determine the effectiveness of disaster simulation on students' knowledge of SDN 1 Soropia about earthquake and tsunami disaster preparedness. With the number of respondents in this study amounted to 86 respondents. The type of research used is a quantitative study with a pre-test and post-test design approach and analyzed using the paired T-test, but previously the data was tested for normality using the Kolmogorov Smirnof test. From the test results before the disaster simulation was carried out, it was found that the respondents said it was ineffective as much as 89.5% and effective as much as 10.5%. Meanwhile, after the disaster simulation was carried out, it was found that 91.9% of respondents said that the disaster simulation was effective for disaster preparedness. Meanwhile, 8.1% said that disaster simulation was not effective for disaster preparedness. From the results of the bivariate test, a p value of 0.000 < 0.05 was obtained, so it was concluded that disaster simulation was effective for disaster preparedness. The advice given to the local government is to empower the local community to be active in disaster preparedness.